Collaborative Governance Dalam Penanggulangan Kekerasan Di Kabupaten Bintan - Jepri Jaya; Novi Winarti; Eki Darmawan (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This research discusses the increasing child violence in Bintan Regency every year. The purpose of this research is to analyze the implementation of collaborative governance in addressing violence against children. The research uses a descriptive qualitative method with data collection techniques through observation, interviews, and documentation. The theory used is the collaborative governance theory by Ansell & Gash, which consists of five indicators: face to face, trust building, commitment to process, shared understanding, and intermediate outcomes. The conclusion of this research shows that collaborative governance in addressing child violence in Bintan Regency has been implemented, with collaboration between the government, child protection agencies, and the community. The indicators of face to face, trust building, and shared understanding have been quite good through communication and coordination among the actors. However, the indicators of commitment to process and intermediate outcomes still face challenges such as changes in positions, sectoral egos, and time constraints. Although services for victims have started to improve, the rate of child violence remains high and many cases are resolved peacefully. An increase in commitment and coordination is needed to strengthen protection efforts and elevate the status of Child-Friendly Districts.